The selective cyclooxygenase-2 inhibitor NS398 ameliorates cisplatin-induced impairments in mitochondrial and cognitive function - Rashid, Mohammad Abdur; Tang, Jason J.; Yoo, Ki-Hyun; Corujo-Ramirez, Ana; Oliveros, Alfredo; Kim, Sang Hoon; Ullah, Faheem; Altawell, Raad; Hawse, John R.; Cole, Peter D.; Jang, Mi-Hyeon (Frontiers in Molecular Neuroscience, 2023)
Chemobrain is a condition that negatively affects cognition in cancer patients undergoing active chemotherapy, as well as following chemotherapy cessation. Chemobrain is also known as chemotherapy-induced cognitive impairment (CICI) and has emerged as a significant medical contingency. There is no therapy to ameliorate this condition, hence identification of novel therapeutic strategies to prevent CICI is of great interest to cancer survivors. Utilizing the platinum-based chemotherapy cisplatin in an investigative approach for CICI, we identified increased expression of cyclooxygenase-2 (COX-2) and prostaglandin E2 (PGE2) in the adult mouse hippocampus, and in human cortical neuron cultures derived from induced pluripotent stem cells (iPSCs). Notably, administration of NS398, a selective COX-2 inhibitor, prevented CICI in vivo without negatively affecting the antitumor efficacy of cisplatin or potentiating tumor growth. Given that dysfunctional mitochondrial bioenergetics plays a prominent role in CICI, we explored the effects of NS398 in cisplatin-induced defects in human cortical mitochondria. We found that cisplatin significantly reduces mitochondrial membrane potential (MMP), increases matrix swelling, causes loss of cristae membrane integrity, impairs ATP production, as well as decreases cell viability and dendrite outgrowth. Pretreatment with NS398 in human cortical neurons attenuated mitochondrial dysfunction caused by cisplatin, while improving cell survival and neurite morphogenesis. These results suggest that aberrant COX-2 inflammatory pathways may contribute in cisplatin-induced mitochondrial damage and cognitive impairments. Therefore, COX-2 signaling may represent a viable therapeutic approach to improve the quality of life for cancer survivors experiencing CICI.